Ventilator-Associated Pneumonia: Outcome in Pediatric Intensive Care Unit of a Tertiary Care Center - Arti Dhingra; Sonia Bhatt; Rajesh Kashyap (Journal of Integrated Health Sciences)
Background: The profile and pattern of ventilator-associated pneumonia (VAP) varies among different settings, depending on the definition, the type of hospital or intensive care unit (ICU), the population studied, and the level of antibiotic exposure. Aim: We aimed to study the profile and pattern of VAP among mechanically ventilated children admitted to a pediatric ICU. Methods: Critically ill children aged 1 month to 12 years of age, who received mechanical ventilation and developed VAP, were included in the study. The VAP was diagnosed using the Clinical Pulmonary Infection Score. The Pediatric Index of Mortality 3 (PIM-3) was also calculated. Categorization of diagnosis was done based on PIM-3 guidelines. The mean length of stay duration of mechanical ventilation was also noted down. Results: The incidence of VAP in the present study was 37.78%. PIM-3 was 2.24. The mean length of stay in cases of early VAP was 8.14 days, whereas it was 20.3 days in late VAP. Two important conditions that led to the development of VAP were respiratory conditions (33.33%) and neurological conditions (27.45%). Liver injury and renal injury were noted in 14 (27.5%) and 10 (19.6%) patients. Significant differences were observed in the mean length of stay and in cases of reintubation. The three most common organisms seen were methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter, and Klebsiella along with Pseudomonas, whereas among nonsurvivors, they were Candida, Citrobacter, Enterococcus spp., methicillin-resistant coagulase-negative staphylococci, and Streptococcus. Conclusion: VAP is a common entity among ventilated children. Cases of late VAP face a longer length of stay on mechanical ventilation. Parenteral nutrition and the presence of nasogastric tubing were significantly associated with late-onset VAP as compared to early VAP. Three most common organisms seen were MRSA, Acinetobacter, and Klebsiella along with Pseudomonas.